Immobilized algae for heavy metals remediation in textile wastewater - Aris Bagus Pradana; Luqman Buchori; Wahyu Diski Pratama; Wahyu Zuli Pratiwi; Hadiyanto (Journal of Emerging Science and Engineering, 2023)
Textile wastewater has characteristics of concentrated color and containing high concentration of COD, BOD, N, P, and heavy metals. Some wastewater treatments have been developed for removal waste contaminant, especially heavy metal such as precipitation, evaporation, electroplating, ion exchange, and membrane process. These methods have disadvantages such as unpredictable of heavy metal, high reagent requirement, and generation of toxic sludge. Biosorption using immobilized algae give the alternative method to removal heavy metal in textile wastewater because of increased stability in the matrix. The main purpose of this research was to determine the adsorption of textile wastewater heavy metal using immobilized microalgae. The best ratio bead: wastewater (v/v) for removal heavy metal by immobilized microalgae of textile wastewater heavy metal in batch system was 1:3. Heavy metal Cu decreased as much as 89% with the highest final concentration of 0.2 ppm. Ability of Chlorella vulgaris and Spirulina platensis to reduce heavy metals Cr was 89% and 90% with a final concentration of 1.6 ppm and 1.5 ppm. Uptake heavy metal Cu and Cr of textile wastewater by Chlorella vulgaris reach 1.9 mg/g and 16.3 mg/g. Meanwhile for Spirulina platensis reach 1.7 mg/g and 14.7 mg/g. Based on the Langmuir equation, biosorption by Chlorella vulgaris have qmax and Kb value of heavy metal Cu was 1,984 mg/g and 0,014 mg/L.  On heavy metal Cr, qmax and Kb value were 15.873 mg/g and 0.079 mg/L. Spirulina platensis have qmax and Kb value of heavy metal Cu were 1,798 mg/g and 0,014 mg/L. On heavy metal Cr qmax and Kb value were 14.925 mg/g and 0.0445 mg/L.